Highly polymorphic microsatellite markers for the Mediterranean endemic fan mussel Pinna nobilis - GONZALEZ-WANGUEMERT, M.; COSTA, J.; BASSO, L.; DUARTE, C.; SERRÃO, E.; HENDRIKS, I. (Mediterranean Marine Science, 2014)
<!-- P { margin-bottom: 0.08in; direction: ltr; color: rgb(0, 0, 0); }P.western { font-family: "Times New Roman",serif; font-size: 10pt; }P.cjk { font-family: "Times New Roman",serif; font-size: 10pt; }P.ctl { font-family: "Times New Roman",serif; font-size: 10pt; }A:link { color: rgb(0, 0, 0); text-decoration: none; } --> Pinna nobilis is an endemic bivalve of the Mediterranean Sea whose populations have decreased in the last decades due to human pressure; as consequence, it was declared a protected species in 1992. Despite its conservation status, few genetic studies using mitochondrial markers have been published. We report on the isolation and development of 10 microsatellite loci for the fan mussel, Pinna nobilis. All loci (2 di-nucleotide, 5 tri-nucleotide, 2 tetra-nucleotide and 1 penta-nucleotide) are characterized by high polymorphism levels in 76 individuals tested from two populations in Balearic Islands (Spain, Western Mediterranean Sea). Number of alleles ranged from 4 to 24 and expected heterozygosity ranged from 0.4269 to 0.9400. These microsatellites could be very useful to assess the genetic diversity and connectivity patterns of P. nobilis and to establish new conservation strategies.